2017
DOI: 10.1155/2017/8456713
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical Mastitis and Distribution of Pathogens in Dairy Farms of Rubavu and Nyabihu Districts, Rwanda

Abstract: A cross-sectional study was conducted from May 2016 to January 2017 in Rubavu and Nyabihu districts, Western Rwanda, aiming at estimating the prevalence of subclinical mastitis (SCM) and identifying its causative bacteria. Management practices and milking procedures were recorded through a questionnaire. 123 crossbreed milking cows from 13 dairy farms were randomly selected and screened for SCM using California Mastitis Test (CMT). Composite CMT positive milk samples were processed for bacterial isolation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 41 publications
10
55
3
1
Order By: Relevance
“…The bacterial pathogens isolated in the present study were dominated by Staphylococcus aureus (Table 2). The prevalence rate of S. aureus (66.15%) in the current study agrees with previous findings reported in Tanzania [34,35,48], Rwanda [31], Algeria [49], Italy [50] and Brazil [51].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The bacterial pathogens isolated in the present study were dominated by Staphylococcus aureus (Table 2). The prevalence rate of S. aureus (66.15%) in the current study agrees with previous findings reported in Tanzania [34,35,48], Rwanda [31], Algeria [49], Italy [50] and Brazil [51].…”
Section: Discussionsupporting
confidence: 92%
“…The overall high prevalence could be attributed to the invisible and silent nature of subclinical mastitis which is usually given little attention by farms when it comes to treatment, and the lack of mastitis control program which has been proved to decrease the prevalence of mastitis in developed countries [40]. However, the prevalence of subclinical mastitis reported in this study is lower than those reported in Uganda [41], Rwanda [31,42,43], Kenya [44], Ethiopia [39] and…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Clinical and subclinical mastitis can be one of the serious consequences of poor milking hygiene [5,7]. Previous studies have shown that the prevalence of mastitis within the East African region is high and that CoNS are common pathogens in bovine mastitis [5,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci are the leading cause of mastitis [5,6], with S. aureus considered to be a major pathogen associated with clinical mastitis and often-recurrent subclinical mastitis, even in well-managed dairy herds. The primary mode of transmission is from cow-to-cow [1].…”
Section: Introductionmentioning
confidence: 99%